The Effect Of Simon Says Game Method On The Listening Ability For The Eighth Grade Students Of MTS AL-WASHLIYAH Serbelawan - Marhaeni K. D Matondang; Rizki Ananda Harahap (Program Studi Pendidikan Bahasa Inggris FKIP, 2022)
This research entitled The Effect of Simon Says Game Method on the Listening Ability for the Eighth Grade Students of MTSS Al-Washliyah Serbelawan. It concered with the problem: Does Simon Says Game Method effect on the listening ability for the eighth grade students of MTSS Al-Washliyah Serbelawan?. To answer the research, some theories are used : (Arikunto, 2014), (Cresswell, 2008), (Nation & Newton, 2009), (Nunan, 2003), (Sudijono, 2017), (Sugiyono, 2013), (Tyagi, 2013) and (Wright, 2006). This research is design into quantitative method by following pre-experimental design of one group pre-test and post-test design. The population is 31 students and the sample is taken by saturated sampling. The instrument is essay test. The data analysis is started from scoring the students’ answer sheets, tabulating students’ pre-test and post-test scores, classifying the students’ listening ability, calculating mean pre-test and post-test, calculating the standard deviation, calculating mean difference and testing hypothesis. Based on the data analysis, it was found that before the treatment od Simon Says Game method, the students’ listening is low since the mean pre-test is 26,45 and low level is dominated. After the treatment, the student’s listening is improved since the mean post-test is 79,03 and good level has been dominated. After analyzing the data, it is calculated that Simon Says Game method effects students’ listening ability for the eighth grade MTSS Al-Washliyah Serbelawan by contributing significant effect value about 52,58. So it is suggested that Simon Says Game effect on the listening ability fot the eighth grade students of MTSS Al -Washliyah Serbelawan in academic year 2021/2022 and should use appropriate method in improving students’ listening ability method